Ownership structure in Brazil: Empirical evidence on the degree of ownership concentration - Dami, Anamélia Borges Tannus; Rogers, Pablo; Ribeiro, Kárem Cristina de Sousa (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This study investigates if there are profit differences, market value, structure of capital, risk and size of assets in relation to the degree of ownership concentration of non-financial Brazilian companies trading in Bovespa from 1997 to 2001. For methodological purpose, the degree of ownership concentration was divided into three categories - disperse, dominant and majoritary - and the differences of the investigated variables were analyzed within those categories, through the statistical methods of Parametric Analysis of Variance and Non-parametric Analysis of Variance. One may conclude that there is more ownership concentration in unstable markets because of the dependence relationship between performance and ownership concentration.